2008
DOI: 10.1111/j.1445-5994.2007.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Job variation in Australian advanced training in neurology

Abstract: Core advanced training jobs in neurology vary considerably across Australia, largely for historical reasons. This situation is suboptimal for many reasons. Training jobs ideally need to be modified to take into account the changing needs of trainees rather than just the service requirements of the various departments, but there are many resource issues involved in achieving this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 5 publications
0
16
1
Order By: Relevance
“…A questionnaire was circulated to all advanced trainees in core training positions in adult neurology in Australia and New Zealand in March, 2012 (). The questionnaire was broadly similar to that which was circulated in 2007 . The survey looked at several different aspects of training including: Ward work: the average number of inpatients looked after by an advanced trainee at any time and the average number of ward consults seen per week. Outpatient clinics: the number of clinics in neurology (both general and specialist) attended per week and the range of specialist clinics available to trainees at their institutions. Neurophysiology exposure: the average number of electroencephalograms (EEG) reported per week and the number of electromyography (EMG) clinics actually attended per week. Out‐of‐hours workload: the average number of hours per week on‐call for general medicine, the number of hours dedicated to neurology on‐call, and the average number of hours of unrostered overtime worked per week. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A questionnaire was circulated to all advanced trainees in core training positions in adult neurology in Australia and New Zealand in March, 2012 (). The questionnaire was broadly similar to that which was circulated in 2007 . The survey looked at several different aspects of training including: Ward work: the average number of inpatients looked after by an advanced trainee at any time and the average number of ward consults seen per week. Outpatient clinics: the number of clinics in neurology (both general and specialist) attended per week and the range of specialist clinics available to trainees at their institutions. Neurophysiology exposure: the average number of electroencephalograms (EEG) reported per week and the number of electromyography (EMG) clinics actually attended per week. Out‐of‐hours workload: the average number of hours per week on‐call for general medicine, the number of hours dedicated to neurology on‐call, and the average number of hours of unrostered overtime worked per week. …”
Section: Methodsmentioning
confidence: 99%
“…Australian advanced trainees undertaking core training in adult neurology were surveyed in 2007 to assess the variability in exposure to various aspects of their training. At that time, there were 38 core training positions located in 28 teaching hospitals across the country . The survey found that there was considerable variation between the training experiences offered by these positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the longer training is made more bearable by remuneration for rostered and unrostered overtime (hours worked over 37.5 hours per week). 10 Although this remuneration is inconsistent from department to department, Australian trainee doctors can usually expect to be paid commensurate to the hours they have worked. This is in comparison to the salaries for American residents, which are generally flat rates regardless of hours worked, unless the resident chooses to moonlight.…”
mentioning
confidence: 99%
“…11 Like in the United States, working hours vary significantly in Australian institutions. In a study of Australian neurology registrars, Lueck et al 10 demonstrated that weekly on-call requirements can range from 1.5 hours of general medicine call to 80 hours of neurology-specific call per week, with significant interhospital variation. The standard median work week was 40 hours (range 21-80), with an average of 8 hours of claimed unrostered overtime.…”
mentioning
confidence: 99%